Práticas discursivas de negociação da face em entrevistas jornalísticas de televisão no estado de Alagoas - Gama, Maria do Carmo Milito (2011)
This research is guided from the perspective of Pragmatics, and it is situated in the theoretical and methodological field of Interactional Sociolinguistics and Conversation Analysis. The objective is to analyze the conversation between participants in a specific type of interaction, that is TV news interviews, conducted in the news of state of Alagoas local TV channels, in order to investigate the saving face process on the run. The theoretical framework is based on studies developed by Goffman (1967) and research work on politeness as an element of saving face developed further by Brown & Levinson (1987). For the research methodology I adopted the proposal of ethnographic microanalysis to analyze in detail each of the interactions recorded in audio and video, through observation and transcription of the conversation, to investigate through the accuracy required, the saving face discursive practice of the interlocutors. The corpus consisted of six interviews that were collected during the initial period of the survey. The results reveal a broad and diverse discursive practice of saving face in the discourse of the interaction in focus. The topic being discussed in every interaction is an element that influences the practice of face saving, especially when taking into account certain contextual components, such as personal/professional identity of the person who is speaking on the topic and its relation with it. The distance from the speech is a resource used repeatedly by both interviewer and interviewee, and there is evidence that a party perceives the occurrence of this practice in the speech of the other. The reaction to cooperate or try to disprove this intention will also vary depending on the contextual elements, not only on who is talking, but mainly from what is being said. In this regard, it was noticed that when the disclosure happens it is not always a threat to face. Finally, it was noticed that politeness is a discursive practice widely used by both parties in the saving face process, and by making use of this practice the interviewer, as one who directs the interaction at first, can achieve the goal of their work as well as mantaining a harmonious interaction with their interviwees.